The Relationship Between Eating Patterns and the Menstrual Cycle of Ambasador High School Students - Anggi Saraswati Putri Dawali; Raden Maria Veronika Widiatrilupi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Menstrual cycle irregularities are a prevalent reproductive health issue among adolescent girls, often linked to dietary imbalances that contribute to hormonal disruption and nutrient deficiencies. This study aimed to analyze the relationship between dietary patterns and menstrual cycles among female students at Ambassador High School. A cross-sectional design was employed with stratified random sampling, involving 30 female students. Data were collected using structured questionnaires covering dietary patterns (frequency, food types, nutritional intake, and eating habits) and menstrual cycle characteristics (regularity, duration, and complaints). The Chi-Square test was used to assess associations between variables at a significance level of p < 0.05. Results indicated that 56.7% of respondents had unbalanced diets characterized by high fast-food consumption, low fruit and vegetable intake, and frequent meal skipping. Menstrual cycle irregularities were reported in 60% of respondents. Statistical analysis revealed a Chi-Square value of 4.420 with a p-value of 0.035, confirming a significant relationship between diet and menstrual cycle. Cross-tabulation showed that 76.5% of students with unbalanced diets experienced irregular cycles compared to 38.5% with balanced diets. These findings highlight the importance of nutrition education and healthy food provision in schools to support adolescent reproductive health.